(untitled) (Revista Educação, Artes e Inclusão, 2021)
Or present study subject as subject to presence of children with deficiency in Infant Education. The objective of the research is to know how the insertion of sessions occurs in some of our children’s education centers. A bibliographic research was carried out in books, scientific articles, dissertations, magazines and, law. Subsequently, an exploratory study I have as resources for the collection of given interviews and questionnaires. A research was carried out in a Child Education Center (CEC), in a municipality of the state of Goiás, Brazil. Participating in the study to the municipal coordinator of the inclusion in Infant Education, to the diretor of the CEC, as seven pedagogues and five support teachers of the same center. The results found show that more and more children with deficiencies are being enrolled in Early Childhood Education and receiving CEC as an award “in hands”. In the meantime, this document can not be a prerequisite for inclusion, but we acknowledge its value for or refer two students to specialized professionals. We conclude that each day that passes the education professions in the municipalities are more aware of their role in the insertion of people with deficiencies, however, there is a long way to go so that the measures established in our law documents on to inclusion of regular schools.